2020
DOI: 10.1108/pm-04-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing and realizing the value of customer-focused property management

Abstract: PurposeThe purpose of this paper is to increase awareness of the value that can be derived from embracing customer service and ensuring tenant satisfaction.Design/methodology/approachThis literature review synthesizes the results of research conducted around the world to examine the value proposition of customer-focused property management. The literature was identified through a search of academic journal articles and industry publications, together with the authors' experience of working with industry practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…For instance, managing a high-rise building requires and prioritizes ensuring the building's security and the occupants' safety (Azian et al, 2020). Additionally, Sanderson et al (2020) noted that, by demonstrating professionalism and property management expertise, fair and ethical execution, excitement and responsiveness to the occupants' needs, managers and residents can build a trusting relationship. Felix (2017) listed four criteria for measuring service quality for assurance, including: making occupants feel safe in their transactions, employees having the knowledge to answer the occupants' questions, consistently courteous employees, and such behavior of employees that instills confidence in the residents.…”
Section: ) Assurancementioning
confidence: 99%
“…For instance, managing a high-rise building requires and prioritizes ensuring the building's security and the occupants' safety (Azian et al, 2020). Additionally, Sanderson et al (2020) noted that, by demonstrating professionalism and property management expertise, fair and ethical execution, excitement and responsiveness to the occupants' needs, managers and residents can build a trusting relationship. Felix (2017) listed four criteria for measuring service quality for assurance, including: making occupants feel safe in their transactions, employees having the knowledge to answer the occupants' questions, consistently courteous employees, and such behavior of employees that instills confidence in the residents.…”
Section: ) Assurancementioning
confidence: 99%
“… Managerial and logistical support: managerial and logistical support attributes can positionally influence residents' satisfaction through several traits. Ease of communication and information dissemination between the residents and building management, both result in enhancing and facilitating improved satisfaction and belongingness (Sanderson and Read, 2020). Residents need to develop a sense of ownership and individuality, through personalizing their living spaces using modality of psych-spatial colors that are reflecting multisensory mechanisms of behavior, this can be further improved by installing decorations, or conducting minor modifications (Stoiljković et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was further reported that management processes and real estate development are also affected by the pandemic. Sanderson and Read (2020) conducted a systematic review of the existing literature while investigating the impact of the Covid-19 pandemic on the property management industry. They focused on the importance of understanding the benefits of customer-centric property management, particularly in the aftermath of the pandemic.…”
Section: Customer-centric Property Management Systemmentioning
confidence: 99%